2012
DOI: 10.1103/physrevb.85.134439
|View full text |Cite
|
Sign up to set email alerts
|

Ordering of the Heisenberg spin glass in four dimensions

Abstract: Ordering of the Heisenberg spin glass in four dimensions (4D) with the nearest-neighbor Gaussian coupling is investigated by equilibrium Monte Carlo simulations, with particular attention to its spin and chiral orderings. It is found that the spin and the chirality order simultaneously with a common correlation-length exponent νCG = νSG ≃ 1.0, i.e., the absence of the spin-chirality decoupling in 4D. Yet, the spin-glass ordered state exhibits a nontrivial phase-space structure associated with a continuous one-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
(73 reference statements)
1
6
0
Order By: Relevance
“…(Such an increase of T dip (L) was indeed observed in a recent simulation of the 4D Heisenberg SG 87 .) The behavior originates from the fact that both the dip and the crossing temperatures of g CG should converge to a common value, T CG , each with an exponent 1/ν and θ(> 1/ν), while the crossing temperature always lies above the dip one.…”
Section: Monte Carlo Resultssupporting
confidence: 75%
“…(Such an increase of T dip (L) was indeed observed in a recent simulation of the 4D Heisenberg SG 87 .) The behavior originates from the fact that both the dip and the crossing temperatures of g CG should converge to a common value, T CG , each with an exponent 1/ν and θ(> 1/ν), while the crossing temperature always lies above the dip one.…”
Section: Monte Carlo Resultssupporting
confidence: 75%
“…While several works [10,11] reported the existence of Heisenberg SG in 3D. Recent study by Kawamura and Nishikawa [3] reported that only a chiral glass exists and no spin glass phase found. These various results indicate that more elaborations on the mechanism of the emergence of SG phenomena are required.…”
Section: Introductionmentioning
confidence: 98%
“…The study of spin glasses has been an active research field for almost four decades [1][2][3][4]. It is a random magnetic system which is mainly characterized by a frozen random spins configuration at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Early numerical study by Coluzzi observed SG phase transition on 4D Heisenberg model. Kawamura and Nishikawa pointed out the absence of Heisenberg SG phase on Ddimensional space, for D ≤ 3 [5]. These works suggested that the lower critical dimension d l might be a fractional number, 3 < d l < 4.…”
Section: Introductionmentioning
confidence: 98%
“…Spin glass (SG) is one of the most complex systems in condensed matter physics and has been intensively studied in the last four decades [1][2][3][4][5][6]. It is a randomly frustrated magnetic system with frozen disordered spin orientation at low temperatures.…”
Section: Introductionmentioning
confidence: 99%